2005
DOI: 10.1073/pnas.0505775102
|View full text |Cite
|
Sign up to set email alerts
|

Cochaperone immunophilin FKBP52 is critical to uterine receptivity for embryo implantation

Abstract: Embryo implantation in the uterus is a critical step in mammalian reproduction, requiring preparation of the uterus receptive to blastocyst implantation. Uterine receptivity, also known as the window of implantation, lasts for a limited period, and it is during this period blastocysts normally implant. Ovarian steroid hormones estrogen and progesterone (P 4) are the primary regulators of this process. The immunophilin FKBP52 serves as a cochaperone for steroid hormone nuclear receptors to govern appropriate ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
208
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 209 publications
(217 citation statements)
references
References 33 publications
8
208
0
1
Order By: Relevance
“…We found that Fkbp52 −/− females on both C57BL6/129 mixed and CD1 backgrounds have implantation failure with normal ovulation (8,9). However, P 4 supplementation rescues implantation and decidualization in CD1, but not in C57BL6/129, Fkbp52 −/− females.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…We found that Fkbp52 −/− females on both C57BL6/129 mixed and CD1 backgrounds have implantation failure with normal ovulation (8,9). However, P 4 supplementation rescues implantation and decidualization in CD1, but not in C57BL6/129, Fkbp52 −/− females.…”
mentioning
confidence: 76%
“…WT and Fkbp52 −/− MEFs (kindly provided by Marc B. Cox, University of Texas, El Paso, TX) were isolated as described previously (8). The cells were maintained in DMEM supplemented with 10% FBS and penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The final mature complex in which the receptor is capable of high affinity hormone binding includes heat shock protein 90 (Hsp90), a 23 kDa cochaperone (p23), and one of a class of proteins (termed FKBPs) characterized by their Hsp90-binding tetratricopeptide repeat (TPR) domain. The 52 kDa FK506 binding protein (FKBP52) associates with receptor-Hsp90 complexes by way of a C-terminal TPR domain and is a specific positive regulator of AR, glucocorticoid receptor (GR), and progesterone receptor (PR) signaling (3)(4)(5). FKBP52 is required for normal male sexual differentiation and development in mice as the fkbp52-deficient mice (52KO) display characteristics of partial androgen insensitivity syndrome including dysgenic prostate (4,6).…”
mentioning
confidence: 99%
“…P 4 signaling inhibits the estrogen signaling pathways in the uterus (Hsueh et al 1975) and this inhibitory relationship involving both hormone pathways orchestrate the regulatory mechanisms required for endometrial receptivity and embryo implantation. Amongst the regulated transcripts in the mid-secretory endometrium from women with mifepristone administration we found several genes involved in the P 4 signaling axis including modulators and effectors with down regulation of NCOA2 (SRC-2, (Mukherjee et al 2006, Jeong et al 2007), IHH (Matsumoto et al 2002, Takamoto et al 2002, ERRFI1 (MIG6, (Kim et al 2010)) PTCH1 (Lee et al 2006) and DKK1 ; and up-regulation of ESR1 (Curtis et al 1999), PRA (Conneely & Lydon 2000), FKBP5 (Tranguch et al 2005), FOXO1A (Kim et al 2005), KLF9 (Simmen et al 2004) and PTGS1 (Wang et al 2004).…”
Section: Discussionmentioning
confidence: 99%